PENGEMBANGAN MEDIA VIDEO KESEHATAN MENTAL PADA GENERASI Z DENGAN DM DI KOTA BANDUNG - Tazqia Dianira Fathima; Febri Sri Lestari (Politeknik Kesehatan Kemenkes Bandung, 2025)
Background: Diabetes Mellitus (DM) is a growing global and national health concern, particularly among Generation Z in Bandung. Beyond physical complications, DM patients often experience mental health issues like anxiety and depression, adversely affecting quality of life and disease progression. Stressed-prone Generation Z individuals are more vulnerable to these psychological impacts. Limited awareness and support worsen the condition, necessitating effective educational media interventions. Preliminary research indicates video media is relevant and motivational for young DM patients. This study aims to develop a mental health video tailored for Generation Z with DM in Bandung. Objective: Develop mental health video media using the 4D approach (Define, Design, Develop, Disseminate) for Generation Z with DM in Bandung. Methodology: This Research and Development (R&D) study employed the 4D model. The Define phase involved interviews with 3 informants to assess media needs. The Develop phase included material expert, media expert, dan 12 respondents selected via purposive sampling. Media feasibility was analyzed using percentage-based evaluation. Results: The Define phase identified key requirements: videos under 5 minutes, portrait format, informal language, and engaging introductions. The Design phase produced a media matrix and storyboard. Feasibility testing showed excellent ratings: 100% (content experts), 91.6% (media experts), and 86.2% (target audience). Dissemination via WhatsApp and TikTok received positive feedback. Conclusion: The video media is highly suitable for mental health education and motivation among Generation Z DM patients in Bandung.